Writing Tasks and Immediate Auditory Memory in Peruvian Schoolchildren - Ventura-León, José Luis (2017)
The purpose of the study is determine the relationship between a group of writing tasks and the immediate auditory memory, as well as to establish differences according to sex and level of study. Two hundred and three schoolchildren of fifth and sixth of elementary education from Lima (Peru) participated, they were selected by a non-probabilistic sample. The Immediate Auditory Memory Test and the Battery for Evaluation of Writing Processes (known in Spanish as PROESC) were used. Central tendency measures were used for descriptive analysis. We employed the Mann-Whitney U test, Spearman Rho test and probability of superiority as effect size measurement for the inferential analysis. The results indicated a moderate direct and significant correlation between writing tasks and immediate auditory memory in general way and low correlations between dimensions. Finally, it showed that the differences in immediate auditory memory and writing tasks according to sex and level of study does not have practical significance.